2004
DOI: 10.2172/891618
|View full text |Cite
|
Sign up to set email alerts
|

The energy-savings potential of electrochromic windows in the UScommercial buildings sector

Abstract: Switchable electrochromic (EC) windows have been projected to significantly reduce the energy use of buildings nationwide. This study quantifies the potential impact of electrochromic windows on US primary energy use in the commercial building sector and also provides a broader database of energy use and peak demand savings for perimeter zones than that given in previous LBNL simulation studies. The DOE-2.1E building simulation program was used to predict the annual energy use of a three-storey prototypical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Moreover, the daylight glare index and lighting energy have been investigated in the context of indoor light to represent the characteristics that can control the range of visible rays [6,9]. According to the results of simulations of office buildings in the United States (US), 10-20% of the energy saving effect is obtained at the perimeters of buildings [10], and at least 54% of the energy can be saved in a Mediterranean climate [11]. A study showed that 37-48% more lighting energy can be saved compared with manual control-type blinds [12].…”
Section: Research Background and Objectivementioning
confidence: 99%
“…Moreover, the daylight glare index and lighting energy have been investigated in the context of indoor light to represent the characteristics that can control the range of visible rays [6,9]. According to the results of simulations of office buildings in the United States (US), 10-20% of the energy saving effect is obtained at the perimeters of buildings [10], and at least 54% of the energy can be saved in a Mediterranean climate [11]. A study showed that 37-48% more lighting energy can be saved compared with manual control-type blinds [12].…”
Section: Research Background and Objectivementioning
confidence: 99%
“…Using the DOE-2.1 software, LBNL conducted, during the same period, another interesting study, which aimed to quantify the potential impact of electrochromic glazing for saving of primary energy in commercial buildings in the United States, in 16 different climate zones in California, and in 6 different climates in the United States (Lee et al, 2004). The simulation was conducted having as a building type the prototype developed by the LBNL for some ASHRAE standards in force in the United States.…”
Section: Research In the Field Of Electrochromic Glazingmentioning
confidence: 99%
“…These features, in general, have led to the development of adaptive building skins, which already prove to have significant operational energy saving potential, by as much as 51% [59,60]. The logic of adaptive performance is compelling: it promotes reduced energy consumption and increased occupant comfort [61]. Although the performance of adaptive enclosures might depend upon the occupant's preferences, its efficacy meets or exceeds that of a fixed system.…”
Section: Application 2: a Dynamic Shell Shading Module For An Adaptivmentioning
confidence: 99%